MASS GAINER POWDER; Helps to increase muscle mass, reduce body fat increases strength & Keeping muscles healthy and optimising their repair to maximise performance - Govind Shukla; Neha S.Giri; D. Sruthi Rao; C.J. Sampath Kumar (International Journal of Pharmacy and Analytical Research, 2022)
Keeping muscles healthy and optimising their repair after training is extremely important in sport to maximise performance. For many sports, it is also desirable to increase muscle mass, reduce body fat overall and increase strength where necessary. This review summarises the current available scientific literature regarding the effect of MASS GAINER POWDER; Helps to increase muscle mass, reduce body fat increases strength & Keeping muscles healthy and optimising their repair to maximise performance.